2009
DOI: 10.1158/0008-5472.sabcs-09-18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obesity on Prognosis after Early Breast Cancer.

Abstract: The annual San Antonio Breast Cancer Symposium (SABCS) is unmatched in its significance with regard to the advancement of breast cancer treatment. It is targeted by many members of the clinical research community as the optimal forum in which to unveil new clinical data. This creates an environment each year where published results from a plethora of ongoing clinical trials lead to the emergence of many new therapeutic agents and changes in the indications for existing treatments across all breast cancer subty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 0 publications
1
53
0
1
Order By: Relevance
“…Overweight/obesity is often associated with the metabolic syndrome and increases the risk of a number of diseases, including hypercholesterolemia and breast cancer . Not only does overweight/obesity influence breast cancer incidence , it also worsens prognosis following breast cancer . The epidemiological and clinically manifested linkage between overweight/obesity and breast cancer is increasingly clear , although important gaps exist in our knowledge.…”
Section: Breast Cancermentioning
confidence: 99%
“…Overweight/obesity is often associated with the metabolic syndrome and increases the risk of a number of diseases, including hypercholesterolemia and breast cancer . Not only does overweight/obesity influence breast cancer incidence , it also worsens prognosis following breast cancer . The epidemiological and clinically manifested linkage between overweight/obesity and breast cancer is increasingly clear , although important gaps exist in our knowledge.…”
Section: Breast Cancermentioning
confidence: 99%
“…With earlier detection and improved treatments, most women will survive breast cancer for at least 5 years . However, obesity (present in over 50% of breast cancer patients) is associated with poor health outcomes for women following a breast cancer diagnosis, including increased risk of recurrence, and disease‐specific and all‐cause mortality . Obesity may also increase the risk of treatment‐related side‐effects, which can persist for many years .…”
Section: Introductionmentioning
confidence: 99%
“…Table 1B lists the characteristics of study subjects according to two BMI categories, non-obese (BMI < 30 kg/m 2 ) and obese (BMI ≥ 30 kg/m 2 ). We have chosen the BMI cutoff of 30 because of well-established associations between poor prognosis and survival of women in the highest BMI categories (4). In the present study, the median BMI of obese women is 31.3 kg/m 2 , while the median BMI of non-obese women is 22.3 kg/m 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown an association between postmenopausal breast cancer risk and excessive body weight, and this association is increased in women with a positive family history of breast cancer (23). In addition, women with breast cancer have an increased risk of dying from breast cancer as well as an increased risk of distant metastasis in obese women (45). …”
Section: Introductionmentioning
confidence: 99%